In the face of spillovers: Prudential policies in emerging economies - Andra Coman; Simon P. Lloyd (European Central Bank (ECB), 2019)
We examine whether emerging market prudential policies help to reduce the macrofinancial spillover effects of US monetary policy. We find that emerging markets with tighter prudential policies face significantly smaller, and less negative, spillovers to total credit from US monetary policy tightening shocks. Loan-to-value ratio limits and reserve requirements appear to be particularly effective prudential measures at mitigating the spillover effects of US monetary policy. Our findings indicate that domestic prudential policies can dampen emerging markets' exposure to US monetary policy and the associated global financial cycle, even when accounting for capital controls, suggesting they may be a useful tool in the face of international macroeconomic policy trade-offs.
Keywords: E52; E58; E61; F44; 330; International spillovers; Local projections; Policy Interactions; Monetary policy; Prudential policy